Geriatric Research – Indian Perspective - Mamta Saini; Indrajeet Singh Gambhir (Journal of the Indian Academy of Geriatrics)
With the rapidly growing older population in India, age-related diseases, disabilities, and socioeconomic issues are also increasing. Providing quality of life to this ever-increasing older population is impossible by any agency or government in the present setup. Geriatric research is a need of the hour in India to provide health care, prevention of disease, and better management of disabilities and maintain the autonomy of our older population.